The effect of antioxidant supplementation on bacterial translocation after intestinal ischemia and reperfusion. (2nd January 2017) - Tassopoulos, A.; Chalkias, A.; Papalois, A.; Iacovidou, N.; Xanthos, T.
ABSTRACT: The intestine is highly sensitive to ischemia/reperfusion (I/R) injury. Intestinal I/R may cause local tissue injury and disruption of the intestinal mucosal barrier, allowing the passage of viable bacteria and endotoxins from the gastrointestinal lumen to distant organs. This phenomenon, known as bacterial translocation (BT), may lead to systemic disorders with high morbidity and mortality. Oxidative stress mediators such as reactive oxygen species, polymorphonuclear neutrophils and nitric oxide are believed to contribute to the intestinal I/R injury. Many antioxidants have shown protective effects against I/R injury of various organs. The present article provides an overview of studies investigating the effect of antioxidant supplementation on BT after intestinal I/R.